2011
DOI: 10.1177/1468087411401548
|View full text |Cite
|
Sign up to set email alerts
|

Fuel reactivity controlled compression ignition (RCCI): a pathway to controlled high-efficiency clean combustion

Abstract: A fuel reactivity controlled compression ignition (RCCI) concept is demonstrated as a promising method to achieve high efficiency – clean combustion. Engine experiments were performed in a heavy-duty test engine over a range of loads. Additionally, RCCI engine experiments were compared to conventional diesel engine experiments. Detailed computational fluid dynamics modelling was then used to explain the experimentally observed trends. Specifically, it was found that RCCI combustion is capable of operating over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
369
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 778 publications
(403 citation statements)
references
References 37 publications
1
369
0
5
Order By: Relevance
“…octane number) stratification [20] [21]. Several studies confirm that in order to achieve high efficiency while reducing NOx and soot emissions, the higher portion of the energy should come from the low reactivity fuel [22] [23]. Taking into account this statement, it is clear that the low reactivity fuel characteristics and its amount in the blend have a significant contribution to the incylinder reactivity, and therefore, to the combustion development and its emissions.…”
Section: Experimental and Numerical Studies Demonstrated That Reactivmentioning
confidence: 99%
See 1 more Smart Citation
“…octane number) stratification [20] [21]. Several studies confirm that in order to achieve high efficiency while reducing NOx and soot emissions, the higher portion of the energy should come from the low reactivity fuel [22] [23]. Taking into account this statement, it is clear that the low reactivity fuel characteristics and its amount in the blend have a significant contribution to the incylinder reactivity, and therefore, to the combustion development and its emissions.…”
Section: Experimental and Numerical Studies Demonstrated That Reactivmentioning
confidence: 99%
“…The consequent increase in temperature and pressure initiates a flame propagation, which proceed gradually from the high to the low reactivity regions of the combustion chamber [22] [34]. In this work, the role of the blend reactivity on combustion progression can be examined comparing two different PERs for the same fuel blend.…”
Section: Low Load Conditionsmentioning
confidence: 99%
“…Recent experimental and simulated studies confirm that RCCI concept allows an effective ignition control and a low maximum PRR (pressure rise rate) while maintaining low engine-out emissions levels and high fuel efficiency simultaneously, proving that the RCCI concept is a more promising LTC technique than HCCI [26] and PPC. In this sense, Kokjohn et al [27] and Splitter et al [28] studied RCCI combustion over a wide range of engine loads and conditions concluding that the main cause of the reduced efficiency at light loads is the reduced combustion efficiency. Thus, it is possible to achieve combustion efficiencies near 98% by reducing the combustion losses, which is considered an acceptable value for a premixed combustion strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, crevices and squish volumes were identified as primary responsible of incomplete combustion. In addition, it was also identified that RCCI concept offers an interesting potential for improving fuel consumption by lowering wall heat transfer [24].…”
Section: Homogeneous Charge Compression Ignition (Hcci) Is a Widely Imentioning
confidence: 99%
“…This combustion mode enables an effective control of the in-cylinder equivalence ratio and reactivity stratification, which allows a flexible operation over a wide operating range. Experimental and simulated studies proved that reactivity controlled compression ignition (RCCI), a dual-fuel diesel-gasoline combustion concept, is a more promising LTC technique than HCCI and PPC [23] [24]. Thus, several investigations have been conducted with the aim of insight into the RCCI phenomena.…”
Section: Homogeneous Charge Compression Ignition (Hcci) Is a Widely Imentioning
confidence: 99%